Cybersecurity challenges in blockchain-based social media networks: A comprehensive review - Muhammad Hasnain; Imran Ghani; David Smith; Ali Daud; Seung Ryul Jeong (Blockchain: Research and Applications)
Blockchain is a disruptive technology that has attracted considerable attention from scholars. The blockchain underlies cryptocurrencies and has rapidly expanded to other areas, including financial transactions and social media networks. However, concerns regarding the information security of social media users still exist regarding blockchain technology. The literature on blockchain online social media (BOSM) networks is growing rapidly because of their critical role in securing users’ information privacy and security. Cybersecurity remains a challenge faced by users on social media networks. Since the publication of BOSM, blockchain has become a widely discussed method for users’ information security. This comprehensive review identifies peer-reviewed articles on BOSM that underpin smart contracts, social media challenges, and research gaps. In this work, Kitchenham’s review guidelines are followed to conduct an in-depth review of the use of blockchain technology in the social media network literature published between January 2016 and March 2024, which reveals a significant increase in publications over the last eight years. A search of major academic databases, including Springer, ScienceDirect, ACM, IEEE Xplore, World Scientific, Taylor & Francis, and Wiley Online, yielded a final pool of 158 articles. The findings of the review indicate key insights concerning the techniques and applications of blockchain technology and challenges for the public via social media networks such as Twitter, Facebook, and Google+. This paper identifies important challenges such as deploying smart contracts, user information privacy, a lack of platform support, users’ reactions to blockchain technology, privacy protection and compensation, security system validation, online disinformation, scalability, and miscellaneous challenges to blockchain technology. Additionally, this review suggests several future research directions to improve the role of blockchain technology in overcoming the challenges of privacy, security, reliability, scalability, and trust in the area of social media networks.